Plumbagin Enhancement by Inducing Roots in Cell Suspension of Plumbago rosea L. Issue 2 (2nd April 2016) - Silja, P. K.; B. Dhanya, Pillai; Satheeshkumar, K.
ABSTRACT: In this study, secondary metabolite production was enhanced by inducing rhizogenesis in cell cultures leading to root culture of Plumbago rosea . Auxins favored rhizogenesis from the cell aggregates, which enhanced the plumbagin production. Combinations of indole-3-butyric acid (1.5 mg.L –1 ) and indole-3-acetic acid (1.0 mg.L –1 ) induced the highest root production (40.0 ± 0.78). Highest biomass and plumbagin (1.33%DW) were obtained when harvested in 40 d.